Pengaruh Gaya Kepemimpinan Kepala Sekolah dan Motivasi Kerja Terhadap Kinerja Guru SMA Negeri di Kecamatan Baturaja Timur - Iid Oktasila; Yunita Sari; Fifian Permata Sari; Anis Feblin (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to analyze the influence of the principal's leadership style on the performance of State High School teachers in East Baturaja District; and explore the influence of work motivation on the performance of State High School teachers in East Baturaja sub-district. The research was conducted at SMA Negeri 1 OKU, SMA Negeri 4 OKU, and SMA Negeri 5 OKU. The research method uses a quantitative descriptive method with total sampling data collection with the samples taken in this research being all ASN teachers in three schools, namely 104 teachers. As for each school: SMA Negeri 1 has 41 teachers, SMA Negeri 4 has 32 teachers and SMA Negeri 5 has 31 teachers. The analytical tool used in this research is multiple linear regression. The results of the research found that the principal's leadership style (X1) influences the performance of teachers (Y) of state high schools in East Baturaja District, with a percentage of 55.5% (correlation table). There is an influence of Work Motivation (X2) on teacher performance (Y) Public High School in East Baturaja District, with a percentage of 52.8% (correlation table). The results of the f test (simultaneous) show that the variables Principal Leadership Style (X1), and Work Motivation (X2) influence teacher performance (Y) State High School in East Baturaja District, The results of the analysis of the coefficient of determination (R2) obtained were 0.382, this shows that the contribution of the influence of the principal's leadership style and work motivation to teacher performance was 38.2% while the remaining 61.8% was influenced by other external variables. This research is about understanding insight, fulfilling needs, and differences, and achieving values. In conclusion, there is a significant influence between leadership style and work motivation on teacher performance. Keywords: Motivation, Principal Leadership Style, Teacher Performance